The role of single-operator cholangioscopy (SpyGlass) in the intraoperative diagnosis of intraductal borders of cholangiocarcinoma proliferation - pilot study - Hajer, Jan; Havlůj, Lukáš; Whitley, Adam; Oliverius, Martin; Gürlich, Robert (Casopis lekaru ceskych, 2019)
Cholangiocarcinoma is a relatively rare, highly fatal neoplasm originating from the biliary epithelium. Its only potentially curative treatment option is a radical surgical resection. The aim of our work was to evaluate the feasibility and the safety of intraoperative ERCP and direct cholangioscopy (SpyGlass) to assess the intraductal border of cholangiocarcinoma proliferation. The study ran from November 2015 to January 2018. The group included patients with histologically verified cholangiocarcinoma and, based on available examinations, the resectability of the tumor was assessed by a multidisciplinary team. In cases of indicated surgical resection we peroperatively performed ERCP with cholangioscopy SpyGlass and "diaphanoscopy" in all patients. The resectability was assessed on the basis of these examinations and the peroperative surgical findings. The resection procedure itself was performed only in 2 out of the total of 14 patients, as other patients were indicated for the implantation of metallic SEMS within the ERCP procedure in the operating room instead. To validate the cholangioscopic findings, we used our own criteria based on both the Monaco and other criteria. We divided the findings according to the presence or absence of ulceration, prominent polyposis, pathological vascularization (4 types), pressure defect with a coagulum in the presence of previous stent implantation, papillomatous changes or discolorations of the mucosa. Out of the total number of 14 patients only two patients were indicated for resection and in both cases R0 resection was achieved. The remaining patients were intraoperatively indicated for palliative implantation of SEMS based on the same unresectable finding during cholangioscopy and laparotomy. We demonstrated the technical feasibility and safety of direct peroperative cholangioscopy. Our results show that direct perioperative cholangioscopy is one of the methods which can contribute to a more accurate determination of tumor spread margins.
Keywords: dospělí; proliferace buněk; nádory žlučových cest; Adult; Bile Duct Neoplasms; Bile Ducts, Intrahepatic; biopsie; direct cholangioscopy; cholangiokarcinom; lidé; Pilot Projects; endoskopie trávicího systému; ERCP; pilotní projekty; Endoscopy, Digestive System; Cholangiocarcinoma; Biopsy; Cell Proliferation; žlučové cesty intrahepatální; cholangiocarcinoma; intraductal ultrasonography; Humans